TELAAH FUNGSIONAL KONSEPSI INSENTIF TERHADAP KEPUASAN KERJA PEGAWAI - Fahmiah Akilah; Danial Rahman (Adaara: Jurnal Manajemen Pendidikan Islam, 2020)
Employee satisfaction of the suitability between the business and the outcome of his work is not necessarily felt by the employees, but not separated from the affect it. Employees will feel satisfied when their work is appreciated. The satisfaction felt by the employees can be determined by various factors, among them is giving incentives. Providing incentives will make employees feel the attention and recognition of achievements that are achieved so that the spirit of work and loyalty will be better. Employee will feel the satisfaction of his job if achievement achieved can be rewarded by giving incentives. Giving incentives to improve employee satisfaction does not only apply to organizations with profit, but also on nonprofit organizations (including educational institutions). Therefore, giving incentives is an important element that needs to be considered when trying to give satisfaction to the employees in their work.